Treatment of abdominal striae distensae in Fitzpatrick skin types IV to V using a 1064‐nm picosecond laser with a fractionated microlens array. Issue 1 (22nd August 2021) - Kaewkes, Arisa; Manuskiatti, Woraphong; Cembrano, Kathryn Anne; Wanitphakdeedecha, Rungsima
Abstract: Background: Striae distensae are atrophic dermal scars that can cause psychosocial distress among affected patients. Despite numerous available therapeutic modalities, no gold standard treatment has been established. Objective: To evaluate the long‐term efficacy and safety of a fractional 1064‐nm picosecond laser for the treatment of striae alba in individuals with dark skin types. Materials and Methods: Twenty volunteers with Fitzpatrick skin types IV–V who presented with striae alba were enrolled. Subjects were treated with a fractional 1064‐nm picosecond laser for four sessions at 4‐week intervals. The skin texture, average melanin index (MI), and melanin variation score were assessed using Antera 3D® before treatment, at 1 month after the second treatment, and at 1, 3, and 6 months after the last treatment. Two independent investigators evaluated clinical improvement by comparing pretreatment and posttreatment photographs. The patient satisfaction rates were likewise assessed. Adverse effects were recorded during the entire study period. Results: Significant improvement of skin texture was seen at 1 month after the final treatment ( p  < 0.001) and continuously improved until the 6‐month follow‐up visit ( p  = 0.003). The average MI significantly increased at 1 month after the final treatment ( p  < 0.001), whereas the melanin variation score decreased throughout the follow‐up period. Investigator assessment at the 6‐month follow‐up revealed that 90% of subjects had moderate to marked improvement of striae appearance. Only two of 20 subjects (10%) developed transient postinflammatory hyperpigmentation (PIH) after laser treatment. Conclusion: Fractional picosecond 1064‐nm laser is effective and well‐tolerated for the treatment of striae alba in dark‐skinned individuals with a low incidence of PIH.